2003
DOI: 10.1002/ajim.10235
|View full text |Cite
|
Sign up to set email alerts
|

Stress factors predicting injuries of hospital personnel

Abstract: This study showed that stressors related to autonomy of work and interpersonal relationship at workplace are predictors of injuries in hospital settings. These factors are potentially amenable to organizational interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 22 publications
4
65
0
1
Order By: Relevance
“…This preventive effect agrees with past findings that interpersonal relations at work affect total injury risk 4,5) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This preventive effect agrees with past findings that interpersonal relations at work affect total injury risk 4,5) .…”
Section: Discussionsupporting
confidence: 92%
“…Injured workers are more likely to report a higher stressors frequency (OR=1.4 (0.9-2.0)), resulting in a monotonic dose-response relationship between stress reaction and injury (p=0.02) 3) . Workers with problems in their interpersonal relationships (RR=1.43; 1.18-1.73) or coworker relationships (RR=1.40; 1.15-1.71) also report greater risk for injury 4) . Specifically, supervisor conflict (RR=2.49 (1.42-4.37)), coworker conflict (RR=2.62; 0.58-4.35), and high emotional demands (RR=2.45; 1.52-3.94) increased injury risk 5) .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, men showed no difference in occupa- tional injury rate according to decision latitude. In hospital workers, the risk for occupational injury was higher in workers with lower job control [Salminen et al, 2003], and female Japanese workers in small-and medium-sized manufacturing enterprises reported a significantly lower job control score than men, which was related to an observable increase in occupational injuries [Nakata et al, 2006]. In some studies, however, no correlation was observed between decision latitude and occupational injury [Murata et al, 2000;Swaen et al, 2004].…”
Section: Discussionmentioning
confidence: 94%
“…Fourth, it is possible that work-related stressors are an intermediated step in a pathway leading from depressive symptoms to the occurrence of occupational injuries. Several studies have demonstrated a relationship between occupational injury and work related stressors [e.g., decision latitude and job demand (Nakata et al 2006;Salminen et al 2003;Swaen et al 2004), low social support (Murata et al 2000;Wilkins and Beaudet 1998), interpersonal conXicts (Greiner et al 1998;Salminen et al 2003), job dissatisfaction (Dembe et al 2004;Holcom et al 1993;Li et al 2001;Nakata et al 2006)]. Conversely, these factors may aVect depressive symptoms, which in turn may work as intervening variables aVecting the occurrence of occupational injuries.…”
Section: Discussionmentioning
confidence: 99%